Development of Gamified Interactive Learning Media for Thermal Concepts to Foster Students’ Conceptual Understanding and Creativity - Nursulistari, Siti; Subali, Bambang; Widiyatmoko , Arif (Universitas Negeri Semarang, 2025)
Science materials at the junior high school level often pose challenges for students, particularly in understanding abstract concepts and differentiating between topics such as temperature, heat, and expansion. These difficulties contribute to low levels of conceptual understanding and limited student creativity. This study aims to develop and evaluate gamification-based interactive science media integrated with the discovery learning model to enhance students’ conceptual understanding and creativity. The study employed a Research and Development (R&D) approach using the ADDIE model and utilized a quasi-experimental design. The participants included 64 seventh-grade students from SMP Negeri 41 Semarang, divided into experimental (class VIIB) and control (class VIIE) groups. The validity assessment yielded high scores for both media (0.90) and material content (0.94). Practicality evaluations demonstrated strong approval from both students (82.97%) and teachers (88.33%). Effectiveness analysis revealed a significant increase in conceptual understanding (N-gain: 0.71, high category) and creativity (N-gain: 0.62, medium category) in the experimental group, while the control group showed lower gains (N-gain: 0.44 and 0.29, respectively). These results indicate that gamified interactive media combined with the discovery learning model is valid, practical, and effective in enhancing students’ conceptual understanding and creativity. This study highlights the potential of integrating gamification into interactive learning environments to foster deeper engagement and improved learning outcomes in science education at the junior high school level. The findings suggest that such innovative approaches can be widely adopted to support active learning and creativity development among students.